(untitled) (Czech Journal of International Relations, 2010)
The study explores the specifics of the Turkish secularism as compared to the general definition of the concept of secularism. By analysing the political and social development of modern Turkey, the author demonstrates the transformation of the Turkish secularism in the face of political and social pressures. From the study’s point of view the Turkish secularism does not represent a static phenomen by any means, but it is rather a changing concept and policy which was profoundly influenced by the notions of Kemalist modernisation and Turkish nationalism above all else. The study presumes that the Turkish secularism remains subject to change and adaptation as these concepts evolve and possibly lose their significance at the cost of other political concepts gaining in significance.